STUDENTS' ERRORS ON THE CIRCLE CONCEPT IN BASIC MATHEMATIC LECTURES - Eyus Sudihartinih (Universitas Brawijaya, 2018)
This study aims to examine student errors on the concept of circles. Researchers conduct explorative study by giving individual written tests (two description questions) to students after learning the concept of circles in basic mathematic lectures. The participants of this study are 46 students of 2015/2016 bacth in the Department of Biology Education of a university in Indonesia. Based on the results of data analysis, more than 75% of the participants experienced errors in the concept of circles. The number of students who experienced errors in problem number 1 in the error categories err1, err2, and err3 respectively 5, 33, and 0 people. While at number 2 error err1, err2, and err3 respectively 1, 37, and 1 person.